2021
DOI: 10.3390/cells10113093
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Lymphatic Interactions Induce CXCR2-CXCL5 Axis and Alter Cellular Metabolism and Lymphangiogenic Pathways to Promote Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA), or cancer of bile duct epithelial cells, is a very aggressive malignancy characterized by early lymphangiogenesis in the tumor microenvironment (TME) and lymph node (LN) metastasis which correlate with adverse patient outcome. However, the specific roles of lymphatic endothelial cells (LECs) that promote LN metastasis remains unexplored. Here we aimed to identify the dynamic molecular crosstalk between LECs and CCA cells that activate tumor-promoting pathways and enhances lymphangioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…It has recently been demonstrated that tumour cells metabolically communicate with stromal cells predominantly in the primary tumour microenvironment. 71 Crosstalk between inflamed lymphatic endothelial cells (LECs) and CCA cells by the CXCL5-CXCR2 axis 72 induces alterations of mitochondrial respiration and glycolysis in tumour cells. Notably, CXCL5 directly induces lactate production, glucose uptake and generation of mitochondrial ROS in CCA cells but also increases metabolic gene expression in LECs.…”
Section: Cca and Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been demonstrated that tumour cells metabolically communicate with stromal cells predominantly in the primary tumour microenvironment. 71 Crosstalk between inflamed lymphatic endothelial cells (LECs) and CCA cells by the CXCL5-CXCR2 axis 72 induces alterations of mitochondrial respiration and glycolysis in tumour cells. Notably, CXCL5 directly induces lactate production, glucose uptake and generation of mitochondrial ROS in CCA cells but also increases metabolic gene expression in LECs.…”
Section: Cca and Glucose Metabolismmentioning
confidence: 99%
“…Significant alterations in the cellular bioenergetics of LECs predispose patients to pro-lymphangiogenic signalling that promotes lymph node metastasis. 72 These lines of evidence paved the way for strategies to target metabolic communications for improved cancer treatments (Fig. 1).…”
Section: Cca and Glucose Metabolismmentioning
confidence: 99%
“…The progression of lung cancer is accelerated by the proliferation, movement, and diffusion of tumor cells. CXCL5 has also been reported to promote tumor progression in different tumors such as gastric cancer ( 60 ), liver cancer ( 62 ), bladder cancer ( 65 ), prostate cancer ( 68 ), nasopharyngeal carcinoma, intrahepatic cholangiocarcinoma ( 58 ), osteosarcoma ( 64 ), cholangiocarcinoma ( 59 ), papillary thyroid carcinoma ( 69 ), and renal cell carcinoma ( 71 ). Notably, CXCL5 also induces the development, metastasis, and drug resistance of bladder cancer.…”
Section: Cxcl5 and Cancermentioning
confidence: 99%
“…Upon CXCR2 stimulation, cancer cells show changes in mitochondrial respiration and in glycolysis, along with the induction of reactive oxygen species, and an increase in glucose uptake and lactate production. In addition, in response to LECs, CCA cells overexpress MMPs, particularly MMP1 and MMP21, resulting in matrix remodeling and further enhancing CCA cell migration and metastasis [ 71 ]. Likely, these molecular mechanisms may favor tumor cell invasion of the lymphatic vasculature and subsequent metastasis to regional lymph nodes.…”
Section: Signals Directing Tumor-associated Lymphangiogenesis and Cel...mentioning
confidence: 99%